The pathogenic c.1171A>G (p.Arg391Gly) and c.2359G>A (p.Val787Ile) ABCC6 variants display incomplete penetrance causing pseudoxanthoma elasticum in a subset of individuals. Issue 12 (15th November 2022) - Szeri, Flora; Miko, Agnes; Navasiolava, Nastassia; Kaposi, Ambrus; Verschuere, Shana; Molnar, Beatrix; Li, Qiaoli; Terry, Sharon F.; Boraldi, Federica; Uitto, Jouni; van de Wetering, Koen; Martin, Ludovic; et al.
Abstract: ABCC6 promotes ATP efflux from hepatocytes to bloodstream. ATP is metabolized to pyrophosphate, an inhibitor of ectopic calcification. Pathogenic variants of ABCC6 cause pseudoxanthoma elasticum, a highly variable recessive ectopic calcification disorder. Incomplete penetrance may initiate disease heterogeneity, hence symptoms may not, or differently manifest in carriers. Here, we investigated whether incomplete penetrance is a source of heterogeneity in pseudoxanthoma elasticum. By integrating clinical and genetic data of 589 patients, we created the largest European cohort. Based on allele frequency alterations, we identified two incomplete penetrant pathogenic variants, c.2359G>A (p.Val787Ile) and c.1171A>G (p.Arg391Gly), with 6.5% and 2% penetrance, respectively. However, when penetrant, the c.1171A>G (p.Arg391Gly) manifested a clinically unaltered severity. After applying in silico and in vitro characterization, we suggest that incomplete penetrant variants are only deleterious if a yet unknown interacting partner of ABCC6 is mutated simultaneously. The low penetrance of these variants should be contemplated in genetic counseling.